Phylogenetic analysis of Indonesian gandaria (Bouea) using molecular markers of cpDNA trnL-F intergenic spacer (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Harsono T, Pasaribu N, Sobir, Fitmawati, Prasetya E.2017. Phylogenetic analysis of Indonesian gandaria (Bouea) using molecular markers of cpDNA trnL-F intergenic spacer. Biodiversitas 18: 51-57.Genus Bouea is a member of the Family Anacardiaceae which is widespread in Malesia region. Genus Bouea consists of two types, namely, B. oppositifolia (Roxb.) Adelb. and B. macrophylla Griffit. This study aims to uncover the genetic diversity of Bouea in Indonesia based on molecular markers of cpDNA trnL-F intergenic spacer. The samples of genetic material analyzed are 7 accessions of B. oppositifolia and 8 accessions of B. macrophylla coming from the collection of the Bogor Botanical Gardens and the field exploration activity in Sumatra, Java, Kalimantan and Ambon, and Anacardium occidentale and Mangifera indica are also used as an out-group comparator. Based on phylogenetic analysis using the maximum parsimony and neighbor-joining method, genus Bouea is a monophyletic group or is derived from the same ancestor. Bouea derived from Gunung Tua, North Sumatra, has the longest branch and showed up earlier than the other sample so it can be considered that the ancestor of genus Bouea. B. oppositifolia has branches longer and show up early so it can be considered the ancestor of B. macrophylla. Both types of genera Bouea grouped separately in the phylogenetic tree and supports grouping types in genera Bouea. The results of phylogenetic tree construction do not indicate a geographical grouping of accession. Based on the phylogenetic tree, genus Bouea has a closer relationship with Anacardium occidentale compared with Mangifera indica. The results showed that the markers cpDNA trnL-F intergenic spacer effectively used to determine relationship in genus Bouea.Keywords: Bouea, cpDNA, gandaria, phylogenetic, trnL-F intergenic spacer
Keywords: Bouea, cpDNA, gandaria, phylogenetic, trnL-F intergenic spacer